Bank panics in transition economies - Juha-Pekka Niinimäki (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
This paper discusses recent bank runs in seven transition economies (Russia, Bulgaria, Estonia, Hungary, Latvia, Lithuania and Romania), comparing them against the older US experience and theoretical research.Bank runs seem to usually be information based.For example, improvements in bank transparency such as new accounting rules can reveal a bank s insolvency and trigger a run. However, bank runs, as seen a few years ago in East Asia, Bulgaria and Russia, may also be accompanied by runs on national currencies. We include a bank run model that shows a bank may issue liquid demand deposits and avoid runs without deposit insurance as long as it also issues less liquid time deposits.Self-fulfilling runs are prevented through elimination of the maturity mismatch.The well-known Diamond & Dybvig (1983) model is modified to account for depositors risk af-finities, whereby high-risk depositors hold their savings as demand deposits and low-risk depositors prefer time deposits.These deposit choices transfer liquidity optimally from low-risk to high-risk depositors who value liquidity.By exploiting these choices, a bank can improve its intertemporal risk-sharing by issuing deposits of varying degrees of liquid-ity. This maturity transformation does not necessarily raise the economy s total liquidity.
URN:NBN:fi:bof-201408071908
Keywords: 330; transition economies; bank panics; bank regulation; financial crises